1998
DOI: 10.1038/bjc.1998.310
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 protein expression: association with p53 and prognosis in colorectal cancer

Abstract: Summary Bcl-2 expression in colorectal carcinomas was studied in a series of 224 patients and the relation to p53 expression, stage and survival assessed. Bcl-2 expression was down-regulated compared with normal mucosa in 67% (151) of the cases. In 144 cases staining was positive for p53 (MAB D07), and 41 of these 144 p53-positive cases were also bcl-2 positive (28%) comeared with 32 of the remaining 80 p53-negative cases (40%). Survival was significantly worse (P = 0.01) in the p53-positive cases. Bcl-2-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 29 publications
2
55
1
2
Order By: Relevance
“…43,44 This correlation was not evident in a larger series of 238 patients. 46 Possibly, high Bcl-2 expression in colorectal cancer is rather associated with low grading and low tumor stage 44,47 than with prognosis or p53 status per se.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…43,44 This correlation was not evident in a larger series of 238 patients. 46 Possibly, high Bcl-2 expression in colorectal cancer is rather associated with low grading and low tumor stage 44,47 than with prognosis or p53 status per se.…”
Section: Discussionmentioning
confidence: 83%
“…As expected, these studies did not see a correlation between p53 alterations and Bcl-2 expression. [43][44][45][46] Paradoxically, patients with tumors expressing Bcl-2 and not p53, were found to have a better prognosis. 43,44 This correlation was not evident in a larger series of 238 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of at least 100 patients with CRC using p53 monoclonal antibodies have generally found that p53 overexpression was associated with worse prognosis. 5,6 This association has not been a consistent observation as some studies have found the opposite, 7 or no correlation. 8,9 However, the majority of DNA sequencing studies have shown a significantly shorter survival time in patients with mutant p53.…”
Section: Colorectal Cancer Biologymentioning
confidence: 82%
“…For example, expression of Bcl-2 delays mammary tumor formation in dimethylbenz(a)anthracene treated mice 21 and hepatocellular carcinoma in c-myc transgenic mice. 22 Studies of human colon cancer [23][24][25][26][27] and breast cancer 28 have demonstrated that Bcl-2 expression is associated with improved survival. For Bax, increased expression in transgenic mice is associated with increased apoptosis and a paradoxical acceleration in lymphoma development in p53 À/À mice.…”
Section: Introductionmentioning
confidence: 99%